PENGARUH AROMATERAPI MAWAR TERHADAP SKALA NYERI DISMENORE PADA REMAJA PUTRI PONDOK PESANTREN MAMBA’UL USHULIL HIKMAH - Pitriyani, Widia; Haniyah, Siti; Safitri, Maya (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p10, 2024)
Dysmenorrhea or menstrual pain is a symptom of pain before or during menstruation caused by an increase in the hormone prostaglandin, which is produced in the lining of the uterus. The aim of the study was to obtain information about the effect of rose aromatherapy on the pain scale of dysmenorrhea in teenage girls at the Mamba'ul Ushulil Hikmah Islamic Boarding School. This type of research is a quantitative type, which applies the pre-experiment method type one-group pretest-posttest design. The sample in the study was in 35 teenage girls boarding school respondents. The sampling technique used the accidental sampling technique with inclusion criteria having never been married and the exclusion criteria being married. Data were obtained through a pretest pain level with a pain scale measurement instrument. The 35 female adolescent respondents were given 3 times rose candle aromatherapy treatment for 60 minutes. So that there is the effect of rose aromatherapy on the dysmenorrhea pain scale in teenage girls at the Mamba'ul Ushulil Hikmah Islamic Boarding School.  The statistical test applied is the Wilcoxon test. The results showed that there was a difference between before and after being given rose candle aromatherapy. The analysis results obtained sig. = 0,000 <0,05.